Rotational-Electron Channeling Contrast Imaging analysis of dislocation structure in fatigued copper single crystal. (15th March 2019) - L'hôte, G.; Lafond, C.; Steyer, P.; Deschanel, S.; Douillard, T.; Langlois, C.; Cazottes, S.
Abstract: The dislocation structure of copper single crystal during cyclic fatigue has been characterized by the Rotational-Electron Channeling Contrast Imaging (R-ECCI) method. This technique is based on the acquisition of series of BackScattered Electron (BSE) images during the sample rotation. It facilitates the determination of orientation conditions in the Scanning Electron Microscope (SEM) for fast and accurate dislocation characterization, regardless of the initial orientation of the sample. The technique was applied to copper, observed in its as-received state as well as after several cyclic fatigue loadings. The evolution of the dislocation structure is described as a function of the applied stress. Graphical abstract: Unlabelled Image